Words The Application of Digital Comic Media ss Proven to Increase Interest in Learning and Nationalistic Attitudes of Senior High School Students - Kustiyuliatin, Sulis Janu Hartati, Viktor Maruli Tua L. Tobing (Journal of Educational Studies, 2025)
The educational system must adapt to the digital age by introducing new ideas to boost student achievement. The transformation of national values as a result of globalization and students' lack of interest, particularly in less engaging topics, pose the greatest problems. So, there has to be educational media that may pique people's attention and make them feel patriotic. Examining the impact of digital comic media on the learning interest and patriotism attitude of class X students at SMA Negeri 1 Kamal is the primary objective of this research. Digital comics are a new kind of educational medium that aims to present complex concepts in a fun and accessible manner. A total of 65 students from both the control and experimental classes made up the study sample. Students' academic interests and patriotic sentiments were assessed using a questionnaire sheet. The researcher arrived at these findings after analysing the data using basic linear regression and independent sample t-tests: 1) Digital comic media influences class X students' enthusiasm in studying at SMA Negeri 1 Kamal, and 2) digital comic media influences class X students' patriotism.